Time to First Line Antiretroviral Therapy Adverse Drug Reaction and its Predictors Among Adult HIV/AIDS Patients on Treatment in Eastern Ethiopia - Weldesenbet, Adisu Birhanu; Tusa, Biruk Shalmeno; Debele, Gebiso Roba; Sisay, Malede Mequanent; Ayele, Tadesse Awoke (Frontiers in Pharmacology, 2022)
Background: Even though determining the time to anti-retroviral therapy (ART) adverse drug reaction and its predictors is a crucial step to overcome the negative consequences of the adverse drug reaction, there is limited information regarding the time to ART adverse drug reaction and its predictors. Therefore, this study aimed to determine the time to first ART adverse drug reaction and its predictors among adult HIV/AIDS patients on first-line antiretroviral therapy in West Hararghe Zone, Eastern Ethiopia. Methods: An institution-based retrospective cohort study was conducted on 561 HIV/AIDS patients on first-line ART from September 2013–January 2019 at public hospitals in West Hararghe Zone, Eastern Ethiopia. Data were collected using checklists and document reviews, entered using Epi Info and analyzed in R software. A Cox proportional hazard model was fitted to identify predictors of the time to first ART adverse drug reaction. Model adequacy was checked using Cox Snell residuals. An adjusted hazard ratio with its confidence interval was used to show the presence and strength of association at a 95% confidence level. Result: Most (90.74%) ART adverse drug reactions occurred within 1 year of initiation of ART. Overall, 54 patients developed ART adverse drug reactions with an incidence density of 3.5/100 persons-years of observations (95% CI: 2.7–4.6). The initial ART regimen (TDF, 3TC, EFV) [AHR = 0.3, 95% CI 0.1–0.7], fair adherence [AHR = 8.8, 95% CI 3.3–23.2], poor adherence [AHR = 7.8, 95% CI 3.1–19.5], moderate body mass index (BMI) at the baseline [AHR = 4.4, 95% CI 1.8–11.0], severe body mass index [AHR = 2.8, 95% CI 1.1–6.8], World Health Organization (WHO) stage II [AHR = 3.7, 95% CI 1.2–11.3] and WHO stage IV [AHR = 6.3, 95% CI 2.0–19.8] were significant predictors of the time to ART adverse drug reactions. Conclusion: In conclusion, most of the ART adverse drug reactions occurred within 1 year of initiation of ART. The initial ART regimen (TDF, 3TC, EFV), adherence, HIV/AIDS stage, and BMI were risk factors for the time to ART adverse drug reaction. The incidence of the antiretroviral therapy adverse reaction was relatively low with early onset. Close monitoring of clients in clinical stage II and above is required and continuous assessment for improving the detection and management of adverse drug reactions is recommended. Patients with poor adherence need to get continuous counseling to improve their adherence status.